Penilaian Information Technology Service Management Sistem Akademik pada Domain Service Operation dengan Pendekatan Framework ITIL V3 - Tarwoto, Tarwoto; Ma'arifah, Windiya; Sarmini, Sarmini (Diponegoro University, 2024)
Information Technology utilization is vital in designing information systems to support business success. Thus, information technology governance becomes very important to produce information systems that are by the vision and mission of higher education institutions. As a technology-based university, Amikom Purwokerto University provides an Academic System to facilitate various academic and non-academic student services. This research was conducted to evaluate the Academic System services of Amikom Purwokerto University with a focus on operational aspects, especially in the Service Operation domain with subdomains request fulfillment process and incident management process. The services provided by the Academic System positively impact students and related parties. Still, there is often a connection failure problem on the server caused by inadequate operations and server overload. This research uses the Information Technology Infrastructure Library Version 3 (ITIL-V3) Framework, specifically the Service Operation subdomain, to assess and improve the maturity level of IT service management. This research found that the Academic System is at level 4 (managed) through maturity level calculations, showing efficiency in work processes and incident handling. By implementing recommended improvements to the request fulfillment and incident management process, this research aims to increase the IT service maturity level towards level 5 (optimized), reflecting the highest level of maturity and excellence. In conclusion, these improvements will deliver maximum value to the business and users, ensuring that Academic Systems executes processes and continues to implement improvements and innovations to remain relevant and high-performing in a dynamic environment.